Kaplan–Meier curve showing 24-month cumulative primary patency stratified by venographic and procedural factors. - Chang Hoon Oh (16786347) (2025)
Each graph shows the cumulative primary patency rates among patients with and without specific risk factors. Differences in the survival distribution were assessed using log-rank tests. A. Venous stenosis. Patients with stenosis ≥50% showed significantly lower patency compared to those with <50% stenosis (p < 0.001). B. Venous spur. Presence of luminal irregularity (spur) was associated with inferior patency outcomes (p < 0.001). C. Persistent Collateral Veins. Patients without collateral flow demonstrated significantly higher patency rates than those with persistent collateral flow (p = 0.001). D. Stent placement. Patients who underwent stent placement had a higher long-term patency than those who did not (p = 0.019). E. Stent diameter. Among patients with stent placement, no significant difference in patency was observed between stents ≤12 mm and >12 mm in diameter (p = 0.332).